The potential impact of the labour relations act 66 of 1995 on organised labour and labour organisation in the Western Cape agricultural sector - Westgarth-Taylor, Lara Nicola (Institute of Development and Labour Law, 2023)
This dissertation looks at the history of farmworker organisation on farms in the Western Cape, and factors which have played a role in the demise and the growth of the union movement in the last few decades. In particular it focuses on the role which legislation has played, and will play, in influencing trade union activity in this sector. The new Labour Relations Act 66 of 1995 (hereinafter referred to as the LRA) affords farmworkers a host of new rights, which are inevitably going to impact upon labour relations on farms. The dissertation looks critically at this legislation, and whether or not the underlying aims of the act are capable of being adequately realised in the agricultural sector. The LRA provides a number of opportunities for trade unions, which agricultural unions may struggle to access. The suggestion in this dissertation is that farmworker trade unions are going to have to operate more strategically in this sector, if they hope to achieve maximum benefit from the LRA for their members. Possible strategies for fannworker unions are discussed in this dissertation, which may make it easier for unions to advance the interests of their members, and make a greater impact in certain sectors within agriculture. Unfortunately however, not all workers in agriculture are going to benefit from organisation, in light of the peculiar difficulties which rural organisations experience in accessing fanns. The LRA strongly favours workers who are unionised, and the result is that non-unionised workers are going to he severely prejudiced if they do not have access to trade unions. The dissertation looks at initiatives in the rural sectors which have emerged to ensure that agricultural workers are not left out in the cold as a result of the union-bias of the legislation.